Research on RFID anti-collision hybrid algorithm based on discrete processing - Ping LI; Li-min SUN; Jia-ying WU; Qing FANG; Jin-yang XIE; Bo-xiang ZHOU (Tongxin xuebao)
A kind of binary tree search algorithms have distinct application limitations such as high number of requests in case that a fairly large number of tags are available.A hybrid anti-collision algorithm was proposed,combining binary tree search with discrete processing.Theoretic analysis show that,different from available schemes,the algorithm essentially performs binary tree search not on a single tag,but on models which identify the property of discrete procession.The proposed algorithm fully takes the time of request into account,as well as power consumption and throughput of the system.Simulation result verifies that the algorithm achieves much better performances such as the time of request and throughput than the previous algorithms.